Exploring HR Management Challenges In Religious Educational Institutions Lesson From Madrasa Serajul Uloom India - Dasep Supriatna (Jurnal Riset Multidisiplin Edukasi, 2025)
This study investigates human resource management (HRM) challenges within Madrasa Serajul Uloom, an Indian religious educational institution, using a qualitative case study approach guided by Institutional Theory. Findings reveal HRM practices are significantly shaped by the interplay of coercive pressures from state regulations, mimetic adoption of practices from peer institutions, and strong normative expectations rooted in religious values. This confluence generates tensions between formalization and tradition, leading to specific difficulties in areas like recruitment, compensation, and policy implementation. The research highlights the complex negotiation required to balance legitimacy demands